THE EFFECT OF COMPENSATION AND AFFECTIVE COMMITMENT ON EMPLOYEE PERFORMANCE WITH PERCEIVED ORGANIZATIONAL SUPPORT AS AN INTERVENING VARIABLE AT THE LHOKSEUMAWE CITY REGIONAL SECRETARIAT - Era Ekawati; Faisal Matriadi; Nurfaliza; A. Hadi Arifin; Ikramuddin; Marbawi (CV. Radja Publika, 2025)
This study examines the Influence of Compensation and Affective Commitment on Employee Performance with Perceived Organizational Support (POS) as an Intervening Variable. The sample in this study were 104 employees of the Lhokseumawe City Regional Secretariat Office. Data collected through questionnaires were analyzed using data analysis methods using Structural Equation Modeling (SEM) which was operationalized with the Analysis of Moment Structure (AMOS) tool. The results of the study indicate that employee competence and affective commitment have a significant effect on POS and employee performance. And POS has a direct effect on employee performance. Then in testing the indirect effect, POS was found to play a role as a partial mediating variable in the relationship between competence and affective commitment on employee performance. The results of this study are expected to be important information for organizational leaders in making policies related to the development of employee performance at the Lhokseumawe City Regional Secretariat